2011
DOI: 10.1242/jeb.056648
|View full text |Cite
|
Sign up to set email alerts
|

Behavioural and kinematic components of the fast-start escape response in fish: individual variation and temporal repeatability

Abstract: SUMMARYInter-individual variation in physiological performance traits, which is stable over time, can be of potential ecological and evolutionary significance. The fish escape response is interesting in this regard because it is a performance trait for which interindividual variation may determine individual survival. The temporal stability of such variation is, however, largely unexplored. We quantified individual variation of various components of the escape response in a population of European sea bass (Dic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
90
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 87 publications
(96 citation statements)
references
References 59 publications
4
90
2
Order By: Relevance
“…Although some aspects of fast-start performance in fishes have been found to be independent of certain external factors (Binning et al, 2014;Fu et al, 2015), other fast-start variables have shown context dependency (Domenici, 2010a), and recent studies have indicated that viewing fast-starts as fixed actions is too simple (Abrahams et al, 2007;Domenici, 2010b;Marras et al, 2011;Tytell and Lauder, 2008). Studies of the black goby showed that fish react proportionally to the perceived strength of a stimulus (Turesson et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Although some aspects of fast-start performance in fishes have been found to be independent of certain external factors (Binning et al, 2014;Fu et al, 2015), other fast-start variables have shown context dependency (Domenici, 2010a), and recent studies have indicated that viewing fast-starts as fixed actions is too simple (Abrahams et al, 2007;Domenici, 2010b;Marras et al, 2011;Tytell and Lauder, 2008). Studies of the black goby showed that fish react proportionally to the perceived strength of a stimulus (Turesson et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Fish condition index was calculated following a previous study (Marras et al, 2011) and correlated with average pectoral fin use. Employing methods 1 and 2 to calculate average pectoral fin use, there was no significant correlation between fish condition index and average pectoral fin use (both P>0.11).…”
mentioning
confidence: 99%
“…PFOS exposure in duced a global inhibition of the hypothalamic-pituitary-adrenal (HPA) axis activity, resul ting in de creased corticosterone secretion and re lease (Pereiro et al 2014), and ultimately affecting the antipredator response. Fast-start swimming is typically controlled by the Mauthner cells, a pair of large reticulospinal neurons that receive various sensory inputs and are powered by intracellular stores of adenosine triphosphate (ATP) and creatine phosphate (Reidy et al 2000, Marras et al 2011. From an ecological point of view, fast-start swimming is of great importance for both predator avoidance and prey capture.…”
Section: Discussionmentioning
confidence: 99%